Nebulised hypertonic saline in moderate-to-severe bronchiolitis: a randomised clinical trial. Issue 3 (5th September 2019) - Jaquet-Pilloud, Raphaelle; Verga, Marie-Elise; Russo, Michel; Gehri, Mario; Pauchard, Jean-Yves
Abstract : Objectives: To investigate whether nebulised hypertonic saline (HS) treatment would decrease length of hospital stay (LOS) among infants with moderate-to severe-bronchiolitis compared with standard supportive care (SC). Methods: We conducted an open, multicentre, randomised clinical trial from 1 April 2013 to 31 March 2016, in Swiss children's hospitals. Patients aged 6 weeks to 24 months with a primary diagnosis of moderate or severe bronchiolitis were included. Children with previous episodes of wheezing, cardiac disease, chronic respiratory disease, immunodeficiency, prematurity (gestational age <34 weeks), corticotherapy in the preceding 2 weeks or inhaled bronchodilators within 24 hours before presentation were excluded. Patients were randomised to receive standard SC with nebulisation of 4 mL of 3% sodium chloride every 6 hours versus SSC. Main outcomes and measures were LOS duration of oxygen therapy, transfer to intensive care unit (ICU), readmission within 7 days following discharge and adverse events. Results: 121 children were randomised. No statistically significant differences were found between treatment groups at baseline (age, Wang Score, atopic history, smoking exposure). Children in the HS group had a non-significant difference in length of stay −2.8 hours (−10; 16) compared with the SC group. There were no differences in oxygen therapy duration, transfer to ICU, readmission rate or adverse events. The intervention was discontinued at the parents' request in 16% of the cases. Conclusion: Our study does not support the use of HS nebulisation in children with moderate to severe bronchiolitis. Trial registration number: NCT01812525 .